INOVAÇÃO COLABORATIVA EM GESTÃO DE PESSOAS: RELATO DE UM HACKATHON ENTRE TRIBUNAL REGIONAL ELEITORAL E UNIVERSIDADE - Eduardo Macedo Barboza, Ingrid; Brady Moreira Holanda, Gervina; Saraiva Júnior, Abraão Freires (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
ABSTRACT: This study addresses the research question: How can an open innovation competition — in the Hackathon format — contribute to the co-creation of technological solutions that promote administrative efficiency and align with the guidelines of CNJ Resolution No. 615/2025? From this inquiry, the research examines the experience of the first innovation marathon jointly organized by a Regional Electoral Court [anonymized] and a Federal University [anonymized]. The initiative represents a collaborative and open technological modernization model focused on developing transformative solutions to improve administrative routines within the Court’s Human Resources Secretariat. Originating from a technical cooperation agreement between the institutions, the Hackathon involved undergraduate students from various disciplines in proposing tools to address challenges related to workflow modeling, automation of routines, and data structuring. The study aims to demonstrate that collaboration between academia and the public sector can enhance service efficiency while adhering to the guidelines for innovation and the responsible use of artificial intelligence in the Judiciary. The methodology adopted is a case study, based on a descriptive and systematic approach that integrates theory and practice, combining theoretical frameworks and legislation governing the use of digital technologies — particularly artificial intelligence — within the Judiciary. The findings indicate that universities play a key strategic role in promoting the development and implementation of best administrative practices in support of a more managerial and innovative public administration. KEYWORDS: Hackathon; Open Innovation; People Management; Electoral Justice; Artificial Intelligence.